Oxidative Stability in Oil‐in‐Water Emulsions with Quercetin or Rutin Under Iron Catalysis or Riboflavin Photosensitization. Issue 4 (14th March 2017) - Yi, BoRa; Ka, HaeJung; Kwon, YongJun; Choi, HyungSeok; Kim, Sunghwa; Kim, Jisu; Kim, Mi‐Ja; Lee, JaeHwan
Abstract: The effects of quercetin and rutin on the oxidative stability of oil‐in‐water (O/W) emulsions were tested under riboflavin (RF) photosensitization in the presence or absence of FeCl2 . The degree of oxidation in O/W emulsions was determined by headspace oxygen content, conjugated dienes, and lipid hydroperoxides. Quercetin chelated more metal than did rutin in iron catalyzed O/W emulsions. Generally, 0.1 mM quercetin and rutin was oxidative while 0.5 and 1.0 mM quercetin and rutin was antioxidative in O/W emulsions under RF photosensitization. Depending on the analysis method, the antioxidants had different strengths. The antioxidative or oxidative properties of quercetin and rutin vary in O/W emulsions and depend the quercetin and rutin concentrations and oxidative forces like transition metals, RF photosensitization, or a combination thereof.